INITIAL SKILLS TO BE DEVELOPED IN STUDENTS IN CHEMISTRY - Jobborov Farhod Buriyevich (American Journals, 2024)
This article argues that students' generalized skills in chemistry should be viewed as a feature of action. That is, it has been shown that the generalization and assimilation of each formed skill is based on a certain rule.
Keywords: Students, chemistry, generalization, skill, teaching, sign, model.